A mobile phone solution for ad-hoc hitch-hiking in South Africa - Miteche, Sacha Patrick (Rhodes University, Faculty of Science, Department of Computer Science, 2014)
The purpose of this study was to investigate the use of mobile phones in organizing ad-hoc vehicle ridesharing based on hitch-hiking trips involving private car drivers and commuters in South Africa. A study was conducted to learn how hitch-hiking trips are arranged in the urban and rural areas of the Eastern Cape. This involved carrying out interviews with hitch-hikers and participating in several trips. The study results provided the design specifications for a Dynamic Ridesharing System (DRS) tailor-made to the hitch-hiking culture of this context. The design of the DRS considered the delivery of the ad-hoc ridesharing service to the anticipated mobile phones owned by people who use hitch-hiking. The implementation of the system used the available open source solutions and guidelines under the Siyakhula Living Lab project, which promotes the use of Information and Communication Technology (ICT) in marginalized communities of South Africa. The developed prototype was tested in both the simulated and live environments, then followed by usability tests to establish the viability of the system. The results from the tests indicate an initial breakthrough in the process of modernizing the ad-hoc ridesharing of hitch-hiking which is used by a section of people in the urban and rural areas of South Africa.
Keywords: Cell phones -- Information services; Cell phone users -- South Africa; Hitchhiking -- South Africa; Mobile communication systems -- Social aspects; Digital media -- South Africa; Information technology -- South Africa